Penanaman Karakter Religius Dan Tanggung Jawab Untuk Siswa Kelas 2 MIM PK Kartasura Berdasarkan Buku Doa Yuk Berdo a Bersama Sahabat Bintang - Setiawan, Ricky Dedy, Nur Amalia, S.S., M. Teach (2017)
This study aims to describe (1) religious character building in the 2nd grade students based on the prayer book Yuk rdo'a Bersama Sahabat Bintang, (2)of responsibility character lding of the 2nd grade students of MI Muhammadiyah Kartasura through the activity of memorizing the do'a and hadist using prayer book Yuk Berdo'a Bersama Sahabat Bintang. This search is a type of qualitative research and uses a single case study research design. Data collection techniques are observation, interviews, and documentation. Data analysis techniques are using data reduction, data presentation, and conclusions. The validity of the data in this study are triangulation techniques and source triangulation. The results of this study are (1) The use of prayer book Yuk Berdo'a Bersama Sahabat Bintang in the activity of emorizing prayers and hadiths conducted by second grade students MI Muhammadiyah PK Kartasura was able to strengten the eligious character, (2) of responsibility characters building through the prayer book Yuk Berdo'a Bersama Sahabat Bintang which is held by grade 2 students of MI Muhammadiyah PK Kartasura has been able to run well, there are still shortcomings because it is still implied in the activity, so the character of responsibility has not been fully seen in the attitude of the students.